The effect of leadership style and organizational justice on the performance of Iraqi Academic Staff - Jameel, Alaa Salam (2021)
Performance of academic staff is critical for universities and countries. However, most studies have focused on the performance of employees in business organizations in developed countries. In Iraq, academic staff is migrating to other countries due to injustice and weak leadership as well as weak job satisfaction. The purpose of this study is to investigate the performance of academic staff in Iraqi public universities. The literature as well as the theories that are related to the performance of employees and academic staff were reviewed. Based on the review, this study proposed that leadership style (transformational and transactional) and organizational justice (distributive, procedural and interactional) would have a direct effect on the performance. Further, the study proposed that job satisfaction would mediate the effect of leadership style and organizational justice on the performance of academic staff. The population for this study were nine public universities in Baghdad. A quota sampling technique was employed to collect the data using a questionnaire. A total of 374 questionnaires were distributed to the respondents of which 323 questionnaires were collected. The data was analysed using SPSS version 24.0 and Partial Least Square (PLS) version 3.3.2. A total of 297 complete and valid responses were collected. The measurement model and the structural model were conducted. All the criteria for assessing the measurement model were achieved. Using the structural model, the findings showed that the effect of organizational justice and leadership style on the performance of academic staff were significant. Transformational and transactional also had significant effect on the performance of academic staff. Further, the interactional and distributive justice also had significant effects on the performance of academic staff. Job satisfaction mediated the effect of organizational justice and leadership style on the performance of academic staff. Decision makers have to develop the practices of transformational leadership and justice among the academicians as it could increase the job satisfaction which leads to enhancement in the performance of academic staff.